ANALISIS PERBANDINGAN KINERJA KEUANGAN THE WALT DISNEY CO SEBELUM DAN SESUDAH AKUISISI MARVEL ENTERTAIMENT - Mahersya Christiani Setiadiwiria; Ansella Jovita Teguh; Clarissa Amanda; Nanik Linawati (MANAJEMEN DEWANTARA, 2025)
This research aims to analyze the comparative financial performance of The Walt Disney Company before and after the acquisition of Marvel Entertainment in 2009. This acquisition was a strategic step for Disney to strengthen their content portfolio by presenting iconic characters from Marvel. This research uses a descriptive-comparative quantitative method by observing profitability ratios as the main indicator of financial performance, including Return on Assets (ROA), Return on Equity (ROE), Gross Profit Margin (GPM), Net Profit Margin (NPM), and Return on Invested Capital (ROIC). The data used are financial reports for the five years before the acquisition (2005–2009) and five years after the acquisition (2010–2014), which were analyzed using a weighted average scoring approach. The research results show a significant increase in several profitability ratios after the acquisition, which reflects increased operational efficiency and business synergy.